2002
DOI: 10.1084/jem.20020045
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Murine Plasmacytoid Dendritic Cell Precursors Is Differentially Regulated by FLT3-ligand and Granulocyte/Macrophage Colony-Stimulating Factor

Abstract: Plasmacytoid predendritic cells or type 1 interferon (IFN)-producing cells (IPCs) have recently been identified in mice. Although culture systems giving rise to different murine dendritic cell subsets have been established, the developmental regulation of murine plasmacytoid IPCs and the culture conditions leading to their generation remain unknown. Here we show that large numbers of over 40% pure CD11c+CD11b−B220+Gr-1+ IPCs can be generated from mouse bone marrow cultures with FLT3-ligand. By contrast GM-CSF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
405
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(440 citation statements)
references
References 30 publications
34
405
0
1
Order By: Relevance
“…This anatomical localization and cell surface antigen expression on pDC suggest that pDC migrate from the blood to the lymph nodes through HEV in an L-selectin-dependent manner [47][48][49]. However, it has been reported that CCR7 expression is up-regulated on pDC in response to pathogenic stimuli, and that pDC migrate to the CCR7 ligands CCL19 and CCL21 expressed by stromal cells in the T cell zone and in HEV [29,50,51]. Moreover, TLR signals or type I IFN affect pDC migration via CXCR3L and CCR7 ligand induction [16,17].…”
Section: Validation Of Pdc Conversion Into Cdcmentioning
confidence: 83%
“…This anatomical localization and cell surface antigen expression on pDC suggest that pDC migrate from the blood to the lymph nodes through HEV in an L-selectin-dependent manner [47][48][49]. However, it has been reported that CCR7 expression is up-regulated on pDC in response to pathogenic stimuli, and that pDC migrate to the CCR7 ligands CCL19 and CCL21 expressed by stromal cells in the T cell zone and in HEV [29,50,51]. Moreover, TLR signals or type I IFN affect pDC migration via CXCR3L and CCR7 ligand induction [16,17].…”
Section: Validation Of Pdc Conversion Into Cdcmentioning
confidence: 83%
“…Various populations of DCs and macrophages were expanded in vitro from bone marrow (BM) cells cultured in either FL, GM-CSF, or macrophage colony stimulating factor (M-CSF) as previously described (7,18). Briefly, BM was flushed from the femur and tibia of experimental mice with complete RPMI medium ([CM] 10% fetal calf serum [FCS], 2 mM L-glutamine, 10 mM HEPES, 100 U/ml penicillin, 100 g/ml streptomycin, 10 M 2-mercaptoethanol [2-ME]).…”
Section: Methodsmentioning
confidence: 99%
“…Singlecell suspensions were prepared from thymus and spleen and were analyzed as described previously [14,26]. Dead cells were excluded by staining with PI or 7-amino-actinomycin D (7-AAD).…”
Section: Flowcytometric Analysismentioning
confidence: 99%